Electronic and spin delocalization in a switchable trinuclear triphenylene trisemiquinone bridged Ni3 complex. Issue 82 (26th September 2019) - Wang, Yiting; Lambert, François; Rivière, Eric; Guillot, Régis; Herrero, Christian; Tissot, Antoine; Halime, Zakaria; Mallah, Talal
Abstract : An electro-switchable trinuclear Ni3 -trisemquinone complex with electronic and spin dependent oxidation state delocalization. Abstract : A trinuclear triphenylene trisemiquinone complex containing paramagnetic Ni II is obtained under ambient conditions from the reaction of deprotonated tricatecholate hexahydroxytriphenylene (H6 HHTP) with Ni II capped with a trispyrazolyl borate tridentate ligand. The magnetic and EPR data are consistent with delocalization of the electronic spin over the three Ni II species. The two-electron reduced complex shows an EPR spectrum corresponding to a S = 1/2 species due to a large antiferromagnetic coupling between the radical and only one of the Ni II ions highlighting the localization of the electronic spin. No EPR signal is observed for the one- and three-electron reduced species consistent with the closed shell of the bridging ligand.